2022 25th International Conference on Information Fusion (FUSION) 2022
DOI: 10.23919/fusion49751.2022.9841304
|View full text |Cite
|
Sign up to set email alerts
|

A Tightly-Integrated Magnetic-Field aided Inertial Navigation System

Abstract: A tightly integrated magnetic-field aided inertial navigation system is presented. The system uses a magnetometer sensor array to measure spatial variations in the local magneticfield. The variations in the field are -via a recursively updated polynomial magnetic-field model -mapped into displacement and orientation changes of the array, which in turn are used to aid the inertial navigation system. Simulation results show that the resulting navigation system has three orders of magnitude lower position error a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The contribution of this work is two-fold. Firstly, it extends the groundwork laid out in [24] by providing a thorough derivation and a comprehensive exposition of the proposed algorithm. Additionally, the performance of the proposed algorithm using real-world data was assessed and benchmarked against the state-of-the-art.…”
Section: B Contributionsmentioning
confidence: 86%
See 1 more Smart Citation
“…The contribution of this work is two-fold. Firstly, it extends the groundwork laid out in [24] by providing a thorough derivation and a comprehensive exposition of the proposed algorithm. Additionally, the performance of the proposed algorithm using real-world data was assessed and benchmarked against the state-of-the-art.…”
Section: B Contributionsmentioning
confidence: 86%
“…The model-based odometry approach was further explored in [2], where it was used to estimate both the translation and orientation change of the array. In the subsequent work [24], the authors included the magnetic field model in the state-space description of an INS system and developed a tightly-integrated magnetic-field-aided INS. Simulation results showed that it has a much slower drift rate than stand-alone INS.…”
Section: A Related Workmentioning
confidence: 99%
“…State estimation is ubiquitous not only for automatic control but for virtually every area of science and engineering. It is a necessary component for target tracking [6,7], motion planning [8,9], simultaneous localization and mapping (slam) [10], sensor management [11], model-based control such as model predictive control [12], inertial navigation [13], and more. Regardless of the application, state estimation provides us with a way of extracting additional information from various measurements, e.g., we can succinctly express that velocity is the time derivative of the position, enabling us to estimate both the position as well as the velocity from only measurements of the position.…”
Section: Background and Motivationmentioning
confidence: 99%
“…MIDR WDM-MIDR Average gradient (G/m) Low gradient 6 6.9% 0.9% 0.02 High gradient 0.7% 0.7% 0.13 velocity stationary state on the ground. This inaccuracy is especially emphasized if the person walks very quickly -i.e.…”
Section: Panelmentioning
confidence: 99%